2019
DOI: 10.1002/1348-9585.12039
|View full text |Cite
|
Sign up to set email alerts
|

One-year weight loss maintenance outcomes following a worksite-based weight reduction program among Japanese men with cardiovascular risk factors

Abstract: Objectives Worksite‐based programs present a simple and effective approach to facilitate weight reduction in employees. Despite the importance of 1‐year weight loss maintenance, studies have generally focused on the short‐term effects of weight reduction programs. In addition, little is known about the long‐term weight maintenance outcomes in Asian populations. We examined the long‐term maintenance effects of a worksite‐based weight reduction program among Japanese men with cardiovascular risk factors. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The limitations of this study include the small number of participants, which, on the other hand, facilitated an individual and personal approach to every patient. The number of participants considered in our study is similar to that reported by some previous studies investigating weight loss maintenance following dietary treatment of obesity [107][108][109][110][111][112]. This fact needs to be considered when attempting to apply the findings of the present study to the broader population as a potential public health intervention to manage obesity.…”
Section: Discussionsupporting
confidence: 71%
“…The limitations of this study include the small number of participants, which, on the other hand, facilitated an individual and personal approach to every patient. The number of participants considered in our study is similar to that reported by some previous studies investigating weight loss maintenance following dietary treatment of obesity [107][108][109][110][111][112]. This fact needs to be considered when attempting to apply the findings of the present study to the broader population as a potential public health intervention to manage obesity.…”
Section: Discussionsupporting
confidence: 71%
“…In the Diabetes Prevention Outcome Study, it was found that 40% of the participants who had lost ≥ 5% of their initial body weight after 1 year (in the intensive lifestyle group) had maintained at least 5% weight loss after 15 years of follow-up [8]. On average, no weight regain during a follow-up period of 12 months was reported after a weight loss program of 3 months in a Japanese worksite intervention [9]. In the Look Ahead Study, comparing an intensive lifestyle intervention (ILI) with regular diabetes control, weight regain occurred after 1 year, but at 4 years weight loss was still significantly more pronounced in the ILI group, as was the case after 8 years (ILI −4.7%, control −2.1%) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Authors were contacted to determine this, but no response was received; therefore, these were excluded. This meant 25 articles were included in the review 13,14,39–61 …”
Section: Resultsmentioning
confidence: 99%
“…The interventions were carried out in several different continents, with most conducted in North America (n = 9) 42,[46][47][48][49]51,53,56,57 and Europe (n = 9), 13,39,[43][44][45]50,54,59,60 followed by Asia (n = 4) 40,52,58,61 and Australia (n = 3) (Table 1). 14,41,55 The setting in which the intervention took place varied.…”
Section: Study Characteristicsmentioning
confidence: 99%